Composite material with nano carbon bridge structure as well as preparation method and application of composite material
By using nano-carbon bridge structure composite materials in ORR and OER catalysts, the problems of high prices and poor stability of existing catalysts are solved, and efficient and stable dual-function electrocatalytic performance is achieved, which is suitable for fuel cells and other applications.
Patent Information
- Application Number
- CN202510370568.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-27
- Publication Date
- 2025-07-01
AI Technical Summary
Existing oxygen reduction reaction (ORR) catalysts such as platinum-based catalysts are expensive and have poor stability, which limit the commercialization of fuel cells and other technologies, and the transition metal oxides have poor conductivity and are difficult to use directly.
Composite materials with nanocarbon bridge structures are used as ORR and OER electrocatalysts to grow nanocarbon bridges in situ through microwave-assisted rapid pyrolysis method to form a core-shell structure in which cobalt nanoparticles are coated with carbon, improving conductivity and electrocatalytic performance.
It achieves efficient and stable dual-function catalytic performance of ORR and OER, with the half-wave potential reaching 0.86V, the overpotential difference is minimal, and the peak power density and specific capacity of zinc-air batteries are higher than that of commercial electrocatalysts Pt/C+RuO2.
Smart Images

Figure CN120227872A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic material preparation, and particularly relates to an electrocatalytic material. Background Art
[0002] The oxygen reduction reaction (ORR) is one of the key reactions in energy conversion devices such as fuel cells and metal-air batteries. Platinum-based catalysts are the most widely studied and applied ORR catalysts at present. However, their high cost and poor stability limit the large-scale commercialization of technologies such as fuel cells. Developing inexpensive, efficient, and stable ORR catalysts is an important way to reduce the cost of these power generation technologies while improving their energy conversion efficiency, and thus has important practical significance.
[0003] Although some transition metals (Fe, Co, Ni, Cu, Mn, etc.) exhibit catalytic activity towards the oxygen reduction reaction / oxygen evolution reaction, due to their poor electrical conductivity, especially for metal oxides with high catalytic activity, it is difficult to directly use them. A better solution is to construct metal-organic framework compounds. Metal-organic framework compounds (MOFs) are porous crystalline materials with a three-dimensional network structure formed by metal centers and polydentate organic ligands through coordination bonds, and have unique advantages such as porosity, large specific surface area, regular structure and tunability, and easy functionalization. They show unique physicochemical properties and potential application values in many fields such as adsorption, separation, magnetism, optics, catalysis, hydrogen storage, and molecular recognition. In recent years, due to their unique structures and physicochemical properties, the application of MOFs and their derivatives in electrochemical energy conversion has attracted much attention. MOFs as electrocatalysts have the following remarkable characteristics: (i) They have a highly ordered porous structure with a uniform pore size distribution and a large specific surface area, which is conducive to the dispersion of active components and provides a large number of active sites for electrocatalytic reactions; (ii) The tunability of the pore size, by adjusting the metal center and organic ligand, MOFs materials with various pore sizes from ultra-micropores to mesopores can be obtained, which is conducive to the preparation of complex porous catalysts; (iii) Easy functionalization and modification, which is conducive to the combination of MOFs with other functional substances to prepare composite materials and improve the electrocatalytic performance of MOFs itself; (iv) MOFs can be prepared using several different metals and maintain their original topological structures, etc. These all provide great development space for the design of MOFs electrocatalysts. Although certain progress has been made in the research on MOF-based nanoelectrocatalysts, their research is still in the initial stage, and there are still some problems with MOFs electrocatalysts, such as weak electrocatalytic activity and poor electrocatalytic stability, etc. For example, the application disclosed in Publication No. CN110106518A discloses a composite material for alkaline electrocatalytic hydrogen evolution and its preparation method, but the formed material is a MOF (metal-organic framework), which is prone to collapse at high temperatures, resulting in poor stability; and the pore size is usually limited to micropores and the structure is relatively single, resulting in low electrocatalytic activity. Summary of the Invention
[0004] In view of the above technical problems, the present invention provides a composite material with a nano-carbon bridge structure, a preparation method thereof, and an application thereof.
[0005] To achieve the above object, the technical solution of the present invention is realized as follows:
[0006] A composite material with a nano-carbon bridge structure, which is a core-shell structure connected by nano-carbon bridges; wherein, the inner core in the core-shell structure is cobalt nanoparticles, and the outer shell is a carbon coating layer distributed with cobalt atoms.
[0007] The graphitization degree of the above composite material is 1 - 1.05, and the specific surface area is 192 - 317 m 2 / g.
[0008] The preparation method of the above composite material with a nano-carbon bridge structure is as follows:
[0009] (1) Dissolve Co(NO3)2·6H2O and 2-methylimidazole in methanol respectively to obtain solution A and solution B; add solution B to solution A to obtain a mixed solution; the mixed solution is subjected to mixing, stirring reaction, centrifugation, washing and drying to obtain ZIF-67;
[0010] (2) Grind the ZIF-67 prepared in step (1) and obtain it through microwave reaction in an inert atmosphere.
[0011] The molar ratio of Co(NO3)2·6H2O to 2-methylimidazole in the above mixed solution in step (1) is 1:30 - 50.
[0012] The temperature of the stirring reaction in the above step (1) is room temperature, and the time is 24 - 48 h.
[0013] In the above step (1), methanol is used for washing; the drying temperature is 50 - 70 °C, and the time is 12 - 24 h.
[0014] The temperature of the microwave reaction in the above step (2) is 700 - 900 °C, and the time is 10 - 20 min.
[0015] The application of the above composite material with a nano-carbon bridge structure as an ORR and / OER electrocatalyst.
[0016] A zinc-air battery, which includes the above composite material with a nano-carbon bridge structure.
[0017] The beneficial effects of the present invention are:
[0018] (1) The present invention prepares a composite material with a nano-carbon bridge structure, and this composite material is a core-shell structure connected by nano-carbon bridges; wherein, in the core-shell structure, the inner core is cobalt nanoparticles (Co NPs), and the outer shell is a carbon coating layer distributed with cobalt atoms (Co NPs). In-situ growth of more nano-carbon bridges by microwave pyrolysis promotes the mass transfer of reactants and enhances the electrical conductivity. In addition, the I G / I D ratios of CBCo-700, CBCo-800, and CBCo-900 are 1.04, 1.05, and 1.01 respectively, all exceeding the ratio of ZIF-67-800 (0.96), which indicates that the graphitization degree is improved through the carbonization process by microwave treatment, facilitating the improvement of electrical conductivity and electrocatalytic performance.
[0019] (2) Compared with the commercial electrocatalyst Pt / C+RuO2, the optimized carbon bridge cobalt catalyst (CBCo-800) exhibits an excellent half-wave potential (E 1 / 2 ) of 0.86V vs. RHE, as well as excellent bifunctional electrocatalytic performance, that is, the minimum overpotential difference (ΔE) is 0.696V. This performance stems from the synergistic active centers of cobalt single atoms and nanoparticles, which promote the adsorption of oxygen intermediates and minimize the energy barrier of the rate-determining step (RDS) of the reaction, thereby accelerating the kinetic processes of ORR / OER.
[0020] (3) The peak power density of the zinc-air battery (ZABs) assembled with CBCo-800 prepared by the present invention is 207mWcm -2 , higher than 110mW cm -2 of Pt / C-RuO2. In addition, at a discharge current density of 10mA cm -2 , the specific capacity of CBCo-800 is 794mAh g -1 , exceeding 723mAh g -1 of the Pt / C-RuO2 battery. In addition, the zinc-air assembled with CBCo-800 has good stability and can complete 1950 cycles, lasting for 650 hours, while Pt / C-RuO2 can only cycle 960 times and last for 320 hours.
[0021] (4) The present invention provides an idea for preparing a low-cost, high-performance and durable ORR and OER bifunctional catalyst. The innovative use of the microwave system enables the kilogram-scale production of the CBCo electrocatalyst, and the total mass of the prepared samples reaches 1.07kg, featuring large-scale preparation. Description of the Drawings
[0022] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments of the present invention. For those of ordinary skill in the art, without creative efforts, other drawings can also be obtained based on these drawings.
[0023] Figure 1 Synthesis and characterization of the composite material prepared by the present invention; wherein, (a) is a schematic diagram of the synthesis process; (b) is the SEM image of the composite material CBCo-800 prepared in Example 1; (c) and (d) are the TEM and aberration-corrected HAADF-STEM images of CBCo-800 respectively; (e) is the magnified SEM image of CBCo-800; (f) is the 3D atomic overlapping Gaussian function fitting diagram of Co single atoms in the composite material; the dark field diffraction image (g) and EDS element distribution map (h) of CBCo-800.
[0024] Figure 2 Structure characterization of CBCo-800 prepared in Example 1; wherein, (a) is TEM; (b) is the HRTEM image; (c) and (d) are the crystal plane spacing fringes corresponding to Area1 and Area2 in (b) respectively.
[0025] Figure 3 SEM of the composite material prepared in Comparative Example 1; wherein, (a) is the low magnification image; (b) is the high magnification image.
[0026] Figure 4 High-resolution XPS spectrum of N1s in CBCo-800 prepared in Example 1 (a) and Raman spectra of the composite materials prepared in Examples 1-3 and Comparative Example 1 (b).
[0027] Figure 5 Nitrogen adsorption-desorption curves (a) and pore size distributions (b) of the composite materials prepared in Examples 1-3, Comparative Example 1 and the present invention.
[0028] Figure 6 ORR and OER performances of Examples 1-3, Comparative Example 1 and Pt / C of the present invention; wherein, (a) is the linear sweep voltammetry (LSV) curve at 1600 rpm; (b) is JK and E 1 / 2Value; (c) LSV curves of CBCo-800 at different rotation speeds; (d) corresponding K-L curves and electron transfer numbers of CBCo-800 at different voltages; (e) test results of rotating ring-disk electrode (RRDE) of BCo-800, and corresponding electron transfer numbers and hydrogen peroxide yields; (f) current-time (i-t) curves of CBCo-800 and Pt / C; (g) OER linear sweep voltammetry (LSV) curves of CBCo-700, CBCo-800, CBCo-900, ZIF-67-800 and RuO2; (h) ΔE values between ORR and OER curves of CBCo-700, CBCo-800, CBCo-900, ZIF-67-800 and Pt / C+RuO2; (i) OER current-time (i-t) curves of CBCo-800 and Pt / C.
[0029] Figure 7 OER Tafel slopes of CBCo-700, CBCo-700, CBCo-700, ZIF-67-800 and RuO2.
[0030] Figure 8 Performance of rechargeable zinc-air batteries (ZABs); where (a) is a schematic diagram of ZABs; (b) are the open-circuit potentials of CBCo-800 and Pt / C+RuO2; (c) are the discharge and charge curves of CBCo-800 and Pt / C+RuO2; (d) are the power densities of CBCo-800 and Pt / C+RuO2; (e) is the specific capacity of the zinc-air battery assembled with CBCo-800; (f) is a photo of the LED display driven by the zinc-air battery assembled with CBCo-800; (g) are the galvanostatic charge-discharge curves of the zinc-air battery using CBCo-800 and Pt / C+RuO2. Detailed implementation mode
[0031] Next, the technical solutions in the embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts shall fall within the protection scope of the present invention.
[0032] Example 1
[0033] The preparation method of the composite material with a nano-carbon bridge structure in this example, the synthesis process schematic diagram is as Figure 1 shown in a, and the steps are as follows:
[0034] (1) Preparation of precursor ZIF-67: Dissolve Co(NO3)2·6H2O (0.1 mol) and 2-methylimidazole (4 mol) in 10 mL and 100 mL of methanol respectively to form solution A and solution B. Pour solution B into solution A and stir magnetically at room temperature for 24 hours. Collect the product by centrifugation, wash it with methanol three times, and finally dry it in vacuum at 60 °C for 12 hours to obtain the ZIF-67 precursor.
[0035] (2) Preparation by microwave-assisted rapid pyrolysis: Grind the prepared ZIF-67 into fine powder and load it into a silicon carbide tube. Place the silicon carbide tube in a microwave reactor (power 1000 W, Nanjing Jiequan Microwave Equipment), quickly heat it to 800 °C, keep it warm for 10 minutes, and then cool it to room temperature under N2 atmosphere. Collect the obtained black powder, which is the composite material with a nano-carbon bridge structure, named CBCo-800.
[0036] The microwave synthesis method promoted the formation of a large number of nano-carbon bridges, which connected Co nanoparticles (Co NPs) ( Figure 1 b). This phenomenon is attributed to the local heating caused by microwave radiation, which occurs in a short time, thus catalyzing the growth of nano-carbon bridges connecting Co active centers. Its unique conductive network is conducive to mass / electron transfer during the ORR / OER process. In addition, the internal structure and crystal of CBCo-800 were studied by TEM and HRTEM ( Figure 2 ). It can be observed from Figure 2 that CBCo-800 presents a core-shell structure, in which multiple Co NPs with sizes less than 30 nm are wrapped by a carbon matrix. The crystal plane spacings of the particles and the carbon layer are and corresponding to the (111) and (100) crystal planes of Co respectively. The existence of Co single atoms (Co SA) sites and metallic Co was demonstrated by aberration-corrected high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) ( Figure 1 d). Co NPs and atomic-level Co sites coexist near the carbon matrix. Aberration-corrected HAADF-STEM observations show that Co single atoms present discrete bright spots evenly distributed in the carbon layer ( Figure 1 e). The distribution of Co single atom sites is random. Figure 1 Figure f shows an enlarged three-dimensional Gaussian function fitting mapping diagram within the rectangular box area, effectively illustrating the isolated characteristics of Co single atom sites. Elemental distribution shows that carbon (C), nitrogen (N), and Co are evenly distributed in the CBCo-800 structure ( Figure 1 g-h). In summary, in the composite material prepared by the present invention, Co NPs are wrapped in the carbon substrate, and at the same time, a network of evenly distributed Co single atom sites exists on the carbon substrate.
[0037] Example 2
[0038] The preparation method of the composite material with a nano-carbon bridge structure in this example is as follows:
[0039] (1) Preparation of the precursor ZIF-67: Dissolve Co(NO3)2·6H2O (0.1 mol) and 2-methylimidazole (4 mol) in 10 mL and 100 mL of methanol respectively to form solution A and solution B. Pour solution B into solution A and stir magnetically at room temperature for 24 hours. Collect the product by centrifugation, wash it with methanol 3 times, and finally dry it in vacuo at 60 °C for 12 hours to obtain the ZIF-67 precursor.
[0040] (2) Preparation by microwave-assisted rapid pyrolysis: Grind the prepared ZIF-67 into fine powder and load it into a silicon carbide tube. Place the silicon carbide tube in a microwave reactor (power: 1000 W), rapidly heat it to 700 °C, hold for 10 minutes, and then cool it to room temperature under a N2 atmosphere. Collect the obtained black powder, which is the composite material with a nano-carbon bridge structure, named CBCo-700.
[0041] Example 3
[0042] The preparation method of the composite material with a nano-carbon bridge structure in this example is as follows:
[0043] (1) Preparation of the precursor ZIF-67: Dissolve Co(NO3)2·6H2O (0.1 mol) and 2-methylimidazole (4 mol) in 10 mL and 100 mL of methanol respectively to form solution A and solution B. Pour solution B into solution A and stir magnetically at room temperature for 24 hours. Collect the product by centrifugation, wash it with methanol 3 times, and finally dry it in vacuo at 60 °C for 12 hours to obtain the ZIF-67 precursor.
[0044] (2) Preparation by microwave-assisted rapid pyrolysis: Grind the prepared ZIF-67 into fine powder and load it into a silicon carbide tube. Place the silicon carbide tube in a microwave reactor (power: 1000 W), rapidly heat it to 900 °C, hold for 10 minutes, and then cool it to room temperature under a N2 atmosphere. Collect the obtained black powder, which is the composite material with a nano-carbon bridge structure, named CBCo-900.
[0045] Example 4
[0046] The preparation method of the composite material with a nano-carbon bridge structure in this example is as follows:
[0047] (1) Preparation of precursor ZIF-67: Dissolve Co(NO3)2·6H2O (0.1 mol) and 2-methylimidazole (5 mol) in 10 mL and 100 mL of methanol respectively to form solution A and solution B. Pour solution B into solution A and stir magnetically at room temperature for 48 hours. Collect the product by centrifugation, wash it with methanol three times, and finally dry it under vacuum at 50 °C for 24 hours to obtain the ZIF-67 precursor.
[0048] (2) Preparation by microwave-assisted rapid pyrolysis: Grind the prepared ZIF-67 into fine powder and load it into a silicon carbide tube. Place the silicon carbide tube in a microwave reactor (power 1000 W, Nanjing Jiequan Microwave Equipment), rapidly heat it to 800 °C, hold for 20 minutes, and then cool it to room temperature under N2 atmosphere. Collect the obtained black powder, which is the composite material with a nano-carbon bridge structure, named CBCo-800.
[0049] Example 5
[0050] The preparation method of the composite material with a nano-carbon bridge structure in this example is as follows:
[0051] (1) Preparation of precursor ZIF-67: Dissolve Co(NO3)2·6H2O (0.1 mol) and 2-methylimidazole (3 mol) in 10 mL and 100 mL of methanol respectively to form solution A and solution B. Pour solution B into solution A and stir magnetically at room temperature for 36 hours. Collect the product by centrifugation, wash it with methanol three times, and finally dry it under vacuum at 70 °C for 18 hours to obtain the ZIF-67 precursor.
[0052] (2) Preparation by microwave-assisted rapid pyrolysis: Grind the prepared ZIF-67 into fine powder and load it into a silicon carbide tube. Place the silicon carbide tube in a microwave reactor (power 1000 W, Nanjing Jiequan Microwave Equipment), rapidly heat it to 800 °C, hold for 15 minutes, and then cool it to room temperature under N2 atmosphere. Collect the obtained black powder, which is the composite material with a nano-carbon bridge structure, named CBCo-800.
[0053] Comparative Example 1
[0054] The preparation method of the composite material in this comparative example is different from that in Example 1 in that the heating method is tube furnace heating treatment, and the specific steps are as follows:
[0055] (1) Preparation of precursor ZIF-67: Co(NO3)2·6H2O (0.1 mol) and 2-methylimidazole (4 mol) were separately dissolved in 10 mL and 100 mL of methanol to form solution A and solution B. Solution B was poured into solution A, and the mixture was magnetically stirred at room temperature for 24 hours. The product was collected by centrifugation, washed three times with methanol, and finally dried in vacuum at 60 °C for 12 hours to obtain the ZIF-67 precursor.
[0056] (2) Heat treatment in a tube furnace: After grinding the prepared ZIF-67 into fine powder, it was placed in a tube furnace with a nitrogen atmosphere for heat treatment (the heating rate of the heat treatment was 5 °C / min, the temperature was 800 °C, and the time was 1 h), and the composite material was obtained, denoted as ZIF-67-800. Figure 3 This is the SEM image of ZIF-67-800 prepared in this comparative example. It can be seen from the figure that only through the calcination treatment in the tube furnace, the material presents a regular dodecahedron morphology with an average size of 200 nm.
[0057] Example of implementation effect
[0058] The element distribution, Raman, nitrogen adsorption-desorption performance, and electrochemical performance of the composite materials prepared in Examples 1-3 and Comparative Example 1 were tested and analyzed, and the results are as follows.
[0059] (1) High-resolution XPS spectra and Raman spectra analysis of N 1s
[0060] The chemical composition of the composite materials was comprehensively analyzed by X-ray photoelectron spectroscopy (XPS). Among them, the high-resolution XPS spectrum of N 1s is as shown in Figure 4 a. Among them, the N 1s peak can be divided into five different peaks, which are respectively consistent with pyridine nitrogen (398.4 eV), pyrrole nitrogen (400.6 eV), graphitic nitrogen (401.7 eV), Co-Nx (399.3 eV), and nitrogen oxide. It is known that graphitic nitrogen enhances the limiting current density by effectively weakening the O-O bond. In addition, pyridine nitrogen and Co-Nx are considered to be the active sites of the oxygen reduction reaction (ORR), which is attributed to the positive polarization effect between N and adjacent C and Co atoms.
[0061] The concentration of graphitic carbon in various catalysts was evaluated by the intensity ratio (I G / I D ) of the G band and D band in the Raman spectrum, and the results are as shown in Figure 4 b. Located at 1350 cm -1 and 1580 cm -1The peaks are usually associated with the disordered band (D band) and the graphitic carbon band (G band), respectively. The calculated IG / ID ratios of CBCo-700, CBCo-800, and CBCo-900 are 1.04, 1.05, and 1.01, respectively, all exceeding the ratio of ZIF-67-800 (0.96), indicating that the graphitization degree is improved by the microwave-treated carbonization process. CBCo-800 exhibits the highest graphitization level, which is beneficial to the improvement of conductivity and electrocatalytic performance.
[0062] (2) Nitrogen adsorption-desorption performance
[0063] N2 adsorption-desorption isotherms are used to analyze the pore size distribution and specific surface area of the samples. All samples exhibit type I isotherms, indicating the coexistence of micropores and macropores in the CBCos framework. Figure 5 b shows a hierarchical pore structure, which is crucial for enhancing mass transfer and improving the availability of active sites. The specific surface areas of CBCo-700, CBCo-800, and CBCo-900 are 192, 317, and 292 m 2 g -1 ( Figure 5 a). It is worth noting that CBCo-800 exhibits the highest specific surface area, indicating that it has more active sites available for catalytic reactions.
[0064] (3) Electrochemical performance
[0065] Using a rotating ring-disk electrode (RRDE) / rotating disk electrode (RDE) loaded with the catalyst as the working electrode, a Hg / HgO electrode (1M) and a graphite rod as the reference electrode and counter electrode. 1M nitrogen-saturated KOH solution and 0.1M O2 / N2-saturated KOH solution are used as the OER and ORR electrolytes, respectively. The potential is calibrated by the following formula:
[0066] E vsRHE =E VS Hg / HgO +0.098 + 0.0591pH.
[0067] Disperse 1mg of CBCos, ZIF-67-800, Pt / C, or RuO2 in 100 μL of Nafion solution (0.5 wt%, diluted from 5 wt% Nafion with ethanol) respectively, and ultrasonically treat for 30 minutes to form a homogeneous ink. Subsequently, take 10 μL of the ink and drop-coat it on a pre-polished RRDE (diameter 5.5 mm, area 0.237 cm 2 , for ORR testing) or RDE (diameter 5 mm, area 0.196 cm 2, on the surface of the disk electrode for OER testing). Commercial Pt / C and RuO2 as control standards were prepared by the same method. All tests were carried out at room temperature using a three-electrode system on a CHI-660e electrochemical workstation.
[0068] Oxygen reduction reaction (ORR) test: In a 0.1 M KOH solution saturated with oxygen / nitrogen, the ORR performance was tested by cyclic voltammetry (CV) with a scan rate of 25 mV / s and a potential window of 0.06 - 1.1 V (vs. RHE). Linear sweep voltammetry (LSV) test was carried out under the same electrolyte conditions with a rotation speed range of 400 - 2025 rpm and a scan rate of 10 mV / s; for the rotating ring-disk electrode (RRDE), the ring electrode constant potential was set at 1.35 V (vs. RHE). Chronoamperometry (i-t) test was carried out at a constant potential of 0.65 V (vs. RHE) and a rotation speed of 1600 rpm.
[0069] Calculation of the number of electrons transferred (n): The number of electrons transferred (n) was calculated by the Koutecky-Levich (K-L) equation:
[0070] 1 / j = 1 / j l + 1 / j k = 1 / Bω 1 / 2 / + 1 / j k
[0071] where j represents the measured current density (mA cm -2 ) measured by linear sweep voltammetry (LSV), j l is the diffusion-limited current density, j k is the kinetic current density, ω is the rotation rate of the electrode, where B = 0.2nFC0(D0) 2 / 3 υ -1 / 6 , and the rotation speed unit is rpm. In the formula, n is the number of electrons transferred, F is the Faraday constant (96,485 C mol -1 ), C0(1.2×10 -6 mol cm -3 ), D0(1.9×10 -5 cm 2 s -1 ) are the volume concentration and diffusion coefficient of O2 in 0.1 M KOH respectively, and v(0.01 cm 2 s -1 ) is the kinetic viscosity of the 0.1 M KOH electrolyte.
[0072] According to the test results of the rotating ring-disk electrode (RRDE), the number of electrons transferred (n) and the hydrogen peroxide yield (H2O2%) can be calculated by the following formula:
[0073]
[0074] Among them, I D is the disk electrode current, and I R is the ring electrode current. The RRDE is 38%.
[0075] Oxygen evolution reaction (OER) test: In a 0.1 M nitrogen-saturated KOH solution, the OER performance was tested by cyclic voltammetry (CV) with a scanning rate range of 10 - 50 mV / s and a potential window of 0.867 - 0.967 V (vs. RHE). Linear sweep voltammetry (LSV) test was carried out in a 0.1 M oxygen-saturated KOH solution, measured using a rotating disk electrode (RDE) at a rotation speed of 1600 rpm with a scanning rate of 10 mV / s. Chronoamperometry (i-t) test was carried out at a constant potential of 1.60 V (vs. RHE) and a rotation speed of 1600 rpm.
[0076] Electrochemical impedance spectroscopy (EIS) test: Measurement was carried out at a potential of 1.60 V (vs. RHE), and the frequency range was 10 -5 to 0.01 Hz.
[0077] The CV test preliminarily evaluated the oxygen reduction reaction (ORR) performance of the prepared catalysts. Further analysis of the LSV curves showed that the half-wave potentials (E 1 / 2 ) of CBCo-700, CBCo-800, CBCo-900, ZIF-67-800, and Pt / C were 0.74, 0.86, 0.79, 0.73, and 0.83 V vs. RHE( Figure 6 a). In addition, as Figure 6 shown in K b, the kinetic current density (J -2 ) of CBCo-800 at 0.80 V was 28.99 mA cm -2 , exceeding that of Pt / C at 10.48 mA cm Figure 6 c). The limiting current density of CBCo-800 increased with the increase of rotation speed Figure 6d). The n value of CBCo-800 is approximately 4, which confirms that an efficient four-electron transfer process occurs during the ORR. Rotating ring-disk electrode (RRDE) measurements were also used to study the ORR pathway of CBCo-800. In the potential range of 0.2 to 0.8 V vs. RHE, the average n value exceeds 3.85( Figure 6 e), which is consistent with the n value calculated by K-L analysis. In addition, the hydrogen peroxide yield of CBCo-800 is less than 6%, highlighting its high selectivity for the ideal 4e - reaction pathway.
[0078] The long-term stability of the catalyst is a key parameter for evaluating its practical application. The durability of CBCo-800 and commercial Pt / C catalysts was evaluated by chronoamperometry. As Figure 6 shown in f, the current retention rate of CBCo-800 is 94% after 8 hours of operation, while that of Pt / C is only 81%.
[0079] To evaluate the bifunctional catalytic performance of CBCos, OER tests were carried out in 0.1 M KOH solution. As Figure 6 shown in g, the overpotential of CBCo-800 at a current density of 10 mA cm -2 is 326 mV, which is lower than those of CBCo-700, CBCo-900, and ZIF-67-800, which are 368, 350, and 417 mV, respectively. Notably, the performance of CBCo-800 is comparable to that of RuO2, with an overpotential of 307 mV. In addition, the Tafel slope of CBCo-800 is lower, with a calculated value of 43 mV dec -1 , indicating its favorable OER intrinsic kinetics( Figure 7 ). After 11 hours of i-t measurement( Figure 6 i), the current density retention rate of CBCo-800 is 89%, while that of RuO2 is only 65%.
[0080] The overpotential of the oxygen evolution reaction (OER) at 10 mA cm -2 and the voltage difference (ΔE) between the half-wave potential (E 1 / 2 ) of the oxygen reduction reaction (ORR) are often used to evaluate the bifunctional performance of the catalyst. In Figure 6 h, the CBCo-800 catalyst exhibits the lowest ΔE value of 0.696 V, indicating its excellent bifunctional catalytic performance. Microwave rapid pyrolysis using a silicon carbide (SiC) crucible as a microwave absorption medium, which promotes uniform heating of the precursor, reduces the aggregation of metal nanoparticles, and enhances conductivity by forming nano-carbon bridges.
[0081] Application Example
[0082] The CBCos-800 prepared by the present invention was applied to Zn-air batteries (ZABs). The specific preparation and assembly methods of the batteries are as follows. The schematic diagram of the ZABs is as shown in Figure 8 a:
[0083] (1) The catalyst (CBCos) was dispersed in Nafion solution and ultrasonicated to form a catalyst ink. Then the ink was uniformly coated on carbon cloth and dried to form a catalyst layer (the loading amount of the catalyst was 1.0 mg cm -2 ).
[0084] (2) The carbon cloth coated with the catalyst was used as the air electrode, the zinc plate was used as the anode, and a 6M KOH and 0.2M Zn(Ac)2 solution was used as the electrolyte to assemble a zinc-air battery.
[0085] Pt / C-RuO2 was applied to Zn-air batteries (ZABs). The preparation method of the battery was the same as that of the above-mentioned CBCos-800. The difference was that in step (1), CBCos was replaced with 0.5 mg Pt / C and 0.5 mg RuO2, and the remaining steps were the same.
[0086] The open circuit potential (OPCT, 800 s test) and the first charge-discharge curve (measured by linear sweep voltammetry (LSV) with a scan rate of 5 mV s -1 ) were carried out on a CHI-660e electrochemical workstation. The galvanostatic charge-discharge curve (GCD) was measured at a current density of 10 mA cm for 10 min of discharge and 10 min of charge. In order to obtain the specific capacity, the battery was discharged at a current density of 10 mA cm -2 until the potential reached 0.1 V. All current densities were normalized according to the geometric surface area of the CL. The specific capacity and specific energy density were calculated by the following formula: -2
[0087]
[0088] where C m is the specific capacity, I is the discharge current, U is the average discharge voltage, t is the discharge time before the voltage reaches 0.5 V, and M is the mass of zinc participating in the reaction.
[0089] The open circuit voltages of CBCo-800 and Pt / C-RuO2 were 1.48 V and 1.43 V respectively ( Figure 8 b). The polarization curves and power densities of CBCo-800 and Pt / C-RuO2 are as shown in Figure 8 c-d. The peak power density of CBCo-800 was 207 mW cm -2 , which was higher than 110 mW cm of Pt / C-RuO2 -2 In addition, at a discharge current density of 10 mA cm -2 , the specific capacity of CBCo-800 is 794 mAh g -1 ( Figure 8 e), exceeding that of the Pt / C-RuO2 battery, which is 723 mAh g -1 . In addition, three-section ZABs assembled with the CBCo-800 air electrode can light up a red LED (4.2 V)( Figure 8 f), demonstrating its potential in energy storage applications. Finally, a constant current charge-discharge test was carried out at a current density of 10 mA cm -2 to evaluate the durability of the catalyst. As Figure 8 shown in g, CBCo-800 can complete 1950 cycles, lasting for 650 hours, while Pt / C-RuO2 can only cycle 960 times, lasting for 320 hours. This result indicates the excellent stability of the ZABs assembled with CBCo-800.
[0090] The above are only the preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention shall be included within the protection scope of the present invention.
Claims
1. A composite material having a nanocarbon bridge structure, characterized in that: The composite material is a core-shell structure connected by nano-carbon bridges; wherein the core of the core-shell structure is cobalt nanoparticles, and the outer shell is a carbon coating layer with cobalt atoms distributed thereon.
2. The composite material with a nano-carbon bridge structure according to claim 1, characterized in that: The graphitization degree of the composite material is 1-1.05 and the specific surface area is 192-317 m 2 / g.
3. The method for preparing the composite material having a nano carbon bridge structure according to claim 1 or 2, characterized in that: Here are the steps: (1) A methanol solution containing Co (NO3)2・6H2O and 2-methylimidazole was mixed, stirred, centrifuged, washed and dried to obtain ZIF-67; (2) Grind the ZIF-67 prepared in step (1) and subject it to microwave reaction in an inert atmosphere to obtain the obtained product.
4. The method for preparing the composite material having a nano carbon bridge structure according to claim 3, characterized in that: In the step (1), the molar ratio of Co(NO3)2·6H2O to 2-methylimidazole is 1:30-50.
5. The method for preparing the composite material having a nano carbon bridge structure according to claim 4, characterized in that: The stirring reaction in step (1) is carried out at room temperature for 24-48 hours.
6. The method for preparing the composite material having a nano carbon bridge structure according to claim 5, characterized in that: In step (1), methanol is used for washing; the drying temperature is 50-70° C. and the drying time is 12-24 h.
7. The method for preparing the composite material having a nano carbon bridge structure according to claim 6, characterized in that: The temperature of the microwave reaction in step (2) is 700-900°C.
8. The method for preparing the composite material having a nano carbon bridge structure according to claim 7, characterized in that: The microwave reaction time in step (2) is 10-20 min.
9. Use of the composite material with nano carbon bridge structure as claimed in claim 1 as an ORR and / or OER electrocatalyst.
10. A zinc-air battery, characterized in that: The zinc-air battery comprises the composite material with a nano-carbon bridge structure according to claim 1.
Citation Information
Patent Citations
Composite material for alkaline electro-catalysis hydrogen evolution and preparation method
CN110106518A